Penyuluhan Gizi Seimbang Serta Penerapan Hidup Bersih dan Sehat di SD Negeri Badean 3 Bondowoso - Agung Nugroho Puspito; Mohammad Ubaidillah; Mohammad Rafli Akbar; Cantika Yaumeilisa Diaz; Sulistya Ayu Safitri; Tria Nofa Nur Imani; Zahra Ayu Ramah Dhani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Nutritional status is an important factor for the health of an individual, community, and the wider community. In Indonesia, the problem of nutrition is still very high. This occurs due to a lack of interest in exploring information about healthy living and balanced nutrition so that meeting daily nutritional needs is not optimal. Based on data from the Ministry of Health, the stunting rate in Indonesia in 2023 was recorded at 21.5 percent, down only 0.1 percent from the previous year which was 21.6 percent. With these problems, we carry out counseling activities with lecture methods and practical assistance to increase the knowledge and awareness of elementary school students, precisely at SD Negeri Badean 3. The material provided regarding healthy living behavior by applying the Balanced Nutrition guidelines includes: The results obtained in this activity are that SD Negeri 3 Badean students are able to understand the balanced nutrition guidelines, Clean and Healthy Living Behavior (PHBS). With this social project, students can already implement healthy living behaviors or also known as a healthy lifestyle in their daily lives.